2019
DOI: 10.3390/su11030709
|View full text |Cite
|
Sign up to set email alerts
|

Green to Gold: Beneficial Impacts of Sustainability Certification and Practice on Tour Enterprise Performance

Abstract: A growing number of managers in tourism recognize the importance of sustainability to their business success. However, as the majority of tourism enterprises consist of small and medium-sized enterprises that are generally less likely to invest in sustainability practices due to a lack of financial resources, time, and perceived cost-saving opportunities, an industry-wide dissemination of sustainability practices is hampered. This paper explores the benefits of adapting sustainability practices and provides ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 53 publications
0
15
0
2
Order By: Relevance
“…Other factors such as the existence of a competitive market environment, the level of innovation of the hotel, social capital and organizational learning also positively influence the green orientation of tourism business organizations and the implementation of sustainability practices [51]. In addition, the literature indicates that sustainability is a beneficial path to follow, regardless of the size, category, and budget of business organizations in the tourism industry [52]. Although most hotels around the world have already adopted environmental sustainability practices, most hotels adopt basic practices, although the scope and extent of these vary with the location of the hotel [53].…”
Section: Environmental and Social Sustainability Practicesmentioning
confidence: 99%
“…Other factors such as the existence of a competitive market environment, the level of innovation of the hotel, social capital and organizational learning also positively influence the green orientation of tourism business organizations and the implementation of sustainability practices [51]. In addition, the literature indicates that sustainability is a beneficial path to follow, regardless of the size, category, and budget of business organizations in the tourism industry [52]. Although most hotels around the world have already adopted environmental sustainability practices, most hotels adopt basic practices, although the scope and extent of these vary with the location of the hotel [53].…”
Section: Environmental and Social Sustainability Practicesmentioning
confidence: 99%
“…Participation in sustainable certification is estimated to affect palm oil companies' performance. Sustainable certification is found to benefit the financial and non-financial performance of companies in various sectors [23]. Additionally, it is found that sustainable certification has several beneficial impacts on companies regarding stock prices [24].…”
Section: Methodsmentioning
confidence: 99%
“…Penelitian atap hijau telah banyak menghasilkan temuan referensi untuk pelbagai bidang disiplin ilmu, diantaranya bidang lingkungan (Agra, Klein, Vasl, Shalom, et al 2017;Hellmeister and Richins 2019;Yang et al 2018;M. A. Hossain et al 2019).…”
Section: Pendahuluanunclassified